Molecular pathogenesis and clinical management of Fanconi anemia - Kee, Younghoon; D’Andrea, Alan D. (The Journal of clinical investigation, 2012)
Fanconi anemia (FA) is a rare genetic disorder associated with a high frequency of hematological abnormalities and congenital anomalies. Based on multilateral efforts from basic scientists and clinicians, significant advances in our knowledge of FA have been made in recent years. Here we review the clinical features, the diagnostic criteria, and the current and future therapies of FA and describe the current understanding of the molecular basis of the disease.